REVITALISASI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN SEBAGAI PEMBANGUN KARAKTER MELALUI PEMBERDAYAAN KULTUR SEKOLAH - Masrukhi Masrukhi (Universitas Negeri Malang, 2016)
Revitalization of the Teaching and Learning of Civic Education: Building a Character by Empowering School Culture. This study was aimed at constructing a teaching and learning model of character building suitable for primary schools. The study was conducted in 89 primary schools in Semarang, Central Java. The study took respondents of 200 teachers whose home base was civic education. The data were obtained using structured-scale questionnaires. The data were analyzed using LISREL. The study came up with two points: the configuration model constructed of exogenous latent variables in the form of teachers' understanding of character building, and the notion that character building was mostly constructed by the schools' culture and the leadership of the school principals.   Revitalisasi Pembelajaran Pendidikan Kewarganegaraan Sebagai Pembangun Karakter Melalui Pemberdayaan Kultur Sekolah Tujuan penelitian adalah membangun model pembelajaran character building yang fit di sekolah dasar. Penelitian dilakukan pada 89 SD di Semarang , dengan responden sebanyak 200 orang guru pengampu Pendidikan Kewarganegaraan. Data dijaring melalui angket skala berstruktu, dan dianalisis dengan menggunakan perangkat LISREL.Penelitian ini menemukan beberapa hal. Pertama model konfigurasi terbangun oleh variable laten eksogen berupa apresiasi guru, kepemimpinan kepala sekolah, kultur sekolah, dan rancangan pembelajaran. Kedua, Kedua, pembangunan karakter, lebih banyak terbangun oleh kultur sekolah dan  kepemimpinan kepala sekolah.